Morphometric variations of Apis dorsata Fabricius (Insecta: Hymnoptera: Apidae) from South Sumatra, Belitung, and West Kalimantan: Variasi morfometrik Apis dorsata Fabricius (Insecta: Hymnoptera: Apidae) dari Sumatera Selatan, Belitung, dan Kalimantan Barat - Besse Fatimah; Rika Raffiudin; Tri Atmowidi; Aulia Savira; Astuti Latif; Windra Priawandiputra (Jurnal Entomologi Indonesia, 2026)
Apis dorsata Fabricius is a giant forest honey bee with a wide distribution that includes Indonesia. South Sumatra, Belitung, and West Kalimantan exhibit distinct geographic and ecological characteristics that may influence the morphometric variations of this species. This study aimed to analyze the similarities and differences across various morphometric parameters of A. dorsata colonies from these three regions. A traditional morphometric approach was conducted to measure 23 morphometric parameters. A total of 120 individuals from 12 A. dorsata colonies originating from South Sumatra, Belitung, and West Kalimantan were examined. The results indicated that 12 of the 23 parameters (52.2%) differed significantly among populations. Populations from South Sumatra generally exhibited larger structural dimensions across several head, thorax, and wing parameters, whereas the Belitung populations demonstrated higher values for proboscis length and antennal socket distance. Multivariate analysis (NMDS and ANOSIM) revealed statistically significant, albeit weak, differentiation among the populations. Overall, these findings indicate the presence of localized morphometric variations across the islands, although the degree of morphological differentiation remains relatively low.